Pelatihan Pengelolaan Gula Semut Di Nagori Silou Buttu Kecamatan Raya Kabupaten Simalungun - Tioner Purba; Ummu Harmain; Marulam MT Simarmata; Triastuti (Universitas, 2022)
Brown sugar is crystallized palm sugar. Some of the reasons why palm sugar is healthier than granulated sugar is that the calories contained in palm sugar are smaller than white sugar so palm sugar is often referred to as low-calorie sugar, and palm sugar also has a lower glycemic index, namely of 35 while in granulated sugar the glycemic index is 58. The optimal way to improve the structure of melted sugar is by processing it into granular sugar, namely through re-melting of molded sugar with the addition of water into a sugar solution. The addition of granulated sugar and seed was found to have an effect on the yield, total sugar, sucrose, and the level of preference for color, taste and aroma, but decreased water content, reducing sugar, browning index and aroma level.The best treatment is the addition of 30% granulated sugar with a seeding temperature of 120 0C, in general it meets the requirements of SII where the water content, 2.75%, reducing sugar 4.35%, sucrose 81.14, total sugar 89.86, ash content, 1 .91%, browning index 0.20 abs/g and 81.36 yield. While the most preferred organoleptic test is the addition of 30% granulated sugar with a seeding temperature of 120 0C with a color value of 6.95, aroma 5.70 and taste 5.70. Economic analysis of melted molded sugar gives a profit of IDR 778,800/month, while improving the quality by processing ant sugar gives a profit of Rp. 1,606,000/month (all inputs are calculated at cost), If the allocation of family labor is categorized as family income plus the use of other materials that are not paid, then the income is Rp. 4,278,000/month for sugar. printing and Rp. 5,456,000/month for ant sugar. The processing of ant sugar is classified as a profitable business with a relatively higher price level than printed sugar